Modern State Regulation of Migration Processes in the Northern Territories Taking into Account Factors of Social Attractiveness - Sergeevna Khaidukova, Ekaterina; Kamilovich Araslanov, Renat (Opción, 2019)
At the modern stage of development in the northern territories it is important to understand what factors of social attractiveness influence migration processes and whether the state is able to manage migrant flows. To this end, it is essential to analyze the current state of migration processes in the northern territories (by the example of the Khanty-Mansiysk Autonomous Okrug – Yugra) and main social factors that influence migration processes. In the article, the authors consider the current state of migration processes in the Khanty-Mansiysk Autonomous Okrug – Yugra, which is characterized by the number of people arriving and leaving the northern territories, and assess the degree of dependence of migration processes on factors of social attractiveness in the northern oil and gas territories. Results, which were obtained and analyzed, reveal factors of social attractiveness for the territories of the oil and gas region. The results of the research allowed the authors to set forth a number of measures aimed to solve the current problems related to the regulation of migration processes in the northern oil and gas region. Proposals specified in the article are recommended for application by public authorities to manage migration processes in the Khanty-Mansiysk Autonomous Okrug – Yugra.